2022
DOI: 10.1038/s41598-022-13154-9
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to phthalate and decreased body mass index of children: a systematic review and meta-analysis

Abstract: Phthalates are well-known endocrine-disrupting chemicals. Many detrimental health effects of phthalates were investigated, but studies on the association of phthalates with obesity in children showed inconsistent results. Thus, this systematic review and meta-analysis were performed to clarify whether prenatal and postnatal exposures to phthalates are associated with physical growth disturbances in children. We performed the systematic review and meta-analysis following the PRISMA 2020 statement guidelines, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…The authors conclude that prenatal exposure to phthalates is associated with a decrease in BMI in children but is not related to body fat percentage. These findings suggest that phthalates may disrupt children's normal muscle development, rather than inducing obesity, as had been raised in other studies (Lee et al, 2022). Therefore, from an epidemiological point of view, although some studies show a relationship between phthalate exposure and obesity, it is still unclear and more prospective studies confirming this trend are needed (Aaseth et al, 2022).…”
Section: Scientific Evidencementioning
confidence: 62%
See 1 more Smart Citation
“…The authors conclude that prenatal exposure to phthalates is associated with a decrease in BMI in children but is not related to body fat percentage. These findings suggest that phthalates may disrupt children's normal muscle development, rather than inducing obesity, as had been raised in other studies (Lee et al, 2022). Therefore, from an epidemiological point of view, although some studies show a relationship between phthalate exposure and obesity, it is still unclear and more prospective studies confirming this trend are needed (Aaseth et al, 2022).…”
Section: Scientific Evidencementioning
confidence: 62%
“…Four of these studies have shown a positive relationship between exposure to phthalates and obesity. In a very recent literature review, Lee et al (2022) studied whether prenatal or postnatal exposure to phthalates is associated with physical growth disorders in children. The authors conclude that prenatal exposure to phthalates is associated with a decrease in BMI in children but is not related to body fat percentage.…”
Section: Scientific Evidencementioning
confidence: 99%
“…Similarly, conflicting results appear in prospective studies investigating the effects of intrauterine exposure to phthalates (based on concentrations in maternal urine during pregnancy) and infantile obesity, with some demonstrating an adverse relationship between maternal exposure and offspring weight gain [ 206 ], some demonstrating neutral [ 210 ] or even beneficial effects [ 210 , 211 ] and others demonstrating phthalate-compound-specific effects [ 209 ]. A recent meta-analysis indicated an overall association of prenatal exposure to the most broadly used di-(2-ethylhexyl)-phthalate with decreased BMI z-scores in infants but no impact on fat mass, suggesting that the correlation between phthalate exposure and BMI is mediated by decreased muscle growth [ 227 ].…”
Section: Evidence From Human Studies Linking Bpa and Phthalates To Ob...mentioning
confidence: 99%
“…Change in auxological data (height, weight, and BMI) in children was reported to be longitudinally induced by phthalates exposure during mother pregnancy [ 140 , 141 ]. However, a recent systematic review and meta-analysis including 22 longitudinal and 17 cross-sectional studies demonstrated that prenatal exposure to DEHP was associated with decreased BMI z-score in children [ 142 ].…”
Section: Edcs and Endocrine Diseases—evidence In Humansmentioning
confidence: 99%